The Density of Coliform Bacteria Indicators of Pollution in the River Right Labuhanbatu Selatan - Yatini, Yatini; Harahap, Arman (Budapest International Research and Critics University, 2021)
Coliform bacteria is a one of a kind negative bacteria that is commonly found marine waters, the presence of coliform bacteria can be an indicator of biology that is important to know the environmental conditions. This study aims to determine the environmental conditions based on biological indicators in the form of an abundance of coliform bacteria in the waters of the River right District Labuhanbatu Selatan. The main ingredient in this study is the River right and sediment. The results of the analysis showed the density of coliform bacteria in the study site ranged from 500-700 colonies/ml for the sample waters and 27-120 MPN/g for sediment samples. The results obtained are still below the quality standard so that the river right in good condition biologically. The presence of coliform bacteria in the river can affect human and biota. So it needs to be considered in the efforts of the management of the coastal environment, particularly in efforts to maintain the sustainability of fisheries resources